Upcycling of Waste Fluororubber to Photocurable High‐Performance Vinyl‐Terminated Liquid Fluororubber by Multifield Coupling One‐Pot Stepwise Reactions - Donghan Li; Lu Yu; Shurui Ning; Ping Li; Changle Chen; Dawei Zhao; Mingyi Liao; Qingshi Meng; Shixin Zhang; Qinghong Fang; Hailan Kang; Long Li; et al. (Advanced Science)
Abstract To address the challenges of recycling and high‐value utilization of waste fluororubbers, an effective method is reported for producing novel photocurable vinyl‐terminated liquid fluororubbers (VTLF) with elevated fluorine content (63.1%), superior temperature resistance (T10% = 335 °C) from commercial waste fluororubbers. The approach employs a streamlined, multifaceted system (oxidative degradation/condensation reaction) integrating microwave, mechanical, and steady‐state temperature fields. This system facilitates both efficient recycling and high‐value transformation of waste fluororubbers. Initially, waste fluororubbers undergo controlled/oxidative degradation induced by alkali and hydrogen peroxide to yield carboxyl‐terminated liquid fluororubbers (CTLF). Subsequently, condensation reaction system efficiently converts carboxyl groups into photoreactive vinyl groups. Ultimately, environmentally friendly and efficient photocuring of VTLF is achieved. The nonthermal effects of microwave fields reduce the total process time to just 1 h. The resulting photocured VTLF exhibits not only the comprehensive properties of conventional fluororubbers but also excellent chemical stability and unique light transmittance (94.21%). This study proposes a green, straightforward upcycling strategy within the circular economy framework to mitigate environmental issues associated with rubber's covalent crosslinking. Furthermore, it opens avenues for designing and synthesizing novel fluoropolymers for diverse applications.